2013
DOI: 10.1111/apa.12264
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorders: head circumference and body length at birth are both relative

Abstract: The differences in relative macrocephaly and microcephaly, as well as in other parameters, between diagnostic subgroups suggest that the presence of several neurological mechanisms plays a role in the later expression of different phenotypes. An increased head circumference-to-body length ratio in newborns may be a factor to follow that could be related to ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…Although consistent with other work 7,8,18,53 on the group level, newborns later diagnosed with ASD did not deviate from typical controls with regard to body or head size, at the individual level, significantly more newborns exhibited both microsomy and microcephaly. These results were present after the effects of gestational age were accounted for and highlight the presence of an increased variability in prenatal somatic growth amongst newborns later diagnosed with ASD 52 .…”
Section: Discussionsupporting
confidence: 91%
“…Although consistent with other work 7,8,18,53 on the group level, newborns later diagnosed with ASD did not deviate from typical controls with regard to body or head size, at the individual level, significantly more newborns exhibited both microsomy and microcephaly. These results were present after the effects of gestational age were accounted for and highlight the presence of an increased variability in prenatal somatic growth amongst newborns later diagnosed with ASD 52 .…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have also suggested the presence of smaller head sizes at birth, 35,36 and both relative macrocephaly and microcephaly have been reported at birth. 37 However, the present study did not find differences in the head/height or head/weight ratios at any age. A lower absolute value of head size at birth was only found among boys; however, the birth weights of boys in the high-TCDD exposed group may have potentially been lower due to dioxin toxicity.…”
Section: Validity Of Dioxin Effectscontrasting
confidence: 80%
“…Thereafter, relative to growth during the first year, there is a rapid deceleration in HC between 12 and 24 mo of age, such that it is normal compared with the controls (24,27,29). HC is relatively increased in comparison with height (24,26,30,31); however, others report that HC is normal (25) or smaller (32) in relation to height. Many (19,21,28,33) have proposed that this atypical and abnormally accelerated growth in HC is due to dysregulation of growth in general rather than of neuronal growth in the brain, and this may serve as an early indicator of vulnerability to autism in children and among their infant siblings with and without a history of autistic regression.…”
Section: Results/current Status Of Knowledgementioning
confidence: 96%